Environmental Influence on the Chromosome Synapsis in Solanum khasianum and Scope for Chromosome Manipulation - Ghose, SK (Bangladesh Journal of Genetics and Biotechnology, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Key words: Solanum khasianum, desynapsis, Asynapsis, Pachytene Bangladesh j. genet. biotechnol. 7(1&2): 11-13 2006 (June & December)